A cross-cultural sensory analysis of skim powdered milk produced from pasture and non-pasture diets. (December 2020) - Cheng, Z.; O'Sullivan, M.G.; Kerry, J.P.; Drake, M.A.; Miao, Song; Kaibo, D.; Kilcawley, K.N.
Graphical abstract: Highlights: Sensory perception and volatile profiles of skim milk powder (SMP) were influenced by bovine diet. Differences in the sensory perception of SMP existed between USA, Chinese and Irish consumers, assessors and panelists. Volatile profiles could distinguish SMP based on diet. Abstract: Understanding potential cross-cultural sensory differences in the perception of Irish dairy products is important for key markets such as the USA and China. As most Irish dairy products are produced from pasture derived milk, this study investigated the impact of pasture and non-pasture diets on the cross cultural sensory perception of skim milk powder (SMP) in Ireland, USA and China. SMP was produced from cows fed outdoors on ryegrass (GRS), ryegrass/white clover (CLV), and indoors on trial mixed rations (TMR). SMP samples were evaluated by Irish (n = 78), USA (n = 100) and Chinese (n = 106) consumers using an identical hedonic sensory acceptance test in Ireland, USA and China. Optimized Descriptive Profiling (ODP) was performed using trained assessors familiar with dairy products in Ireland (n = 25) and China (n = 22), and traditional descriptive analysis was undertaken by a trained panel (n = 7) in the USA. Volatile analysis was undertaken on each SMP sample. Hedonic assessment found that USA consumers preferred SMP derived from TMR, and Irish consumers preferred SMP from either GRS or CLV. Chinese consumers perceived SMP samples differently to the USA and Irish consumers, but preference was not influenced by diet. Both Irish and Chinese trained assessors found it more difficult to discern differences between GRS or CLV SMP, but could differentiate TMR SMP. Irish assessors preferred GRS and CLV SMP. Chinese and Irish assessors had different preferences for many attributes. Trained USA panelists found significant differences, exclusively associating pasture based diets with "cowy/barny" and "cardboard/wet paper" attributes and more intense "grassy/hay" attributes than in TMR SMP. The abundance of ten volatile compounds differed significantly based on diet with acetoin derived from carbohydrate metabolism at much greater abundance in TMR SMP. This study found that sensory perception and volatile profiles of SMP were influenced by diet and differences in sensory perception existed between the three cultural groups. Irish and USA sensory responses aligned with familiarity of dairy products derived from pasture and non-pasture diets, respectively, and Chinese sensory responses differed to Irish and USA responses likely reflecting their lack of familiarity with dairy products.